The Museum Definition: Questioning the Scope and Motives - Šola, Tomislav (Array, 2010)
The paper suggests the need for a major re-conceptualization of museums, so that they are understood as institutions of public memory, or as heritage institutions. Museum is not a place ; it is a relationship between past and present, between what we have been and what we want to be. It cannot be isolated to an institution and distributed to the masses. A museum is an idea, and yet, it is a form of relationship.